2005
DOI: 10.1108/14777270510579314
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit and the implementation of the Ottawa Ankle Rules

Abstract: PurposeTo implement the research‐based Ottawa Ankle Rules in a district hospital and audit their impact on the number and appropriateness of X‐rays for ankle injuries in A&E.Design/methodology/approachThe method used was retrospective data collection, followed by education and prospective data collection on the management of subsequent ankle injuries. The computer records of the first 150 people presenting to A&E with ankle/foot injuries in one month were reviewed to determine whether the patient underwent an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…If the guideline indicates that a radiograph is needed, the nurse can order it according to protocol (Sorensen et al, 2012). Study results indicated that when nurses abided by these principles, a reduction of 30% regarding the number of radiographic requests was noted (Jennings, Newton, Bonner, & Hancock, 2005).…”
Section: Institution-established Protocolmentioning
confidence: 97%
“…If the guideline indicates that a radiograph is needed, the nurse can order it according to protocol (Sorensen et al, 2012). Study results indicated that when nurses abided by these principles, a reduction of 30% regarding the number of radiographic requests was noted (Jennings, Newton, Bonner, & Hancock, 2005).…”
Section: Institution-established Protocolmentioning
confidence: 97%